Μελέτη στη ταχεία ενεργειακή αντιστάθμιση ηλεκτρικής ενέργειας σε απομονωμένα δίκτυα όπως της Αρχής Ηλεκτρισμού Κύπρου για αντιμετώπιση της αυξομείωσης του φορτίου λόγω της ακανόνιστης χρήσης ανανεώσιμων πηγών ενέργειας στο Δίκτυο. - Αντρέου, Αντρέας (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
The accession of Cyprus to the European Union in May 2004 triggered rapid changes in the field of energy production of the country. Since then, Electricity Authority of Cyprus (EAC) had been the only generating / distributing agent of electricity in Cyprus’s market. Ever since, EAC has lost the monopoly of production. Also, Cyprus had the imposition of a fine because of the additional pollutants that were an effect of the use of heavy fuel oil for the operation of conventional power plant units. Based on the above, the use of natural gas as a fuel for the conventional power plants of the EAC as well as the production of electricity with renewable energy sources is essential. Today the production of electricity from renewable energy sources that are connected to the electricity network of the EAC is a fact and goes up to the 6% of the total energy generation. By 2020 Cyprus has the commitment that 13% of the electricity production will be from renewable energy sources and will have priority at the grid according to the TSO policy. This thesis begins with a historical reference of the electricity network in Cyprus. It is followed by a brief description of the power availability and operation mode of conventional power plant units of the EAC. Finally, there is an analysis of the different technologies about electricity production from renewable energy sources, focusing on the advantages and disadvantages of each technology. Onwards, there is a presentation of the problems that the penetration of RES caused in the network of the electricity authority as well as an analysis in detail and report on what actions are taken by the transmission system operator (TSO) in collaboration with the EAC to solve these problems. Also a comparison of Cyprus and Crete is made concerning the potential for electricity production. Finally, in this thesis proposals are made that not only could solve the problems caused by the penetration of renewables, in Cyprus’s grid, but also use most of the electricity production from RES, so we can have financial benefits as well. Out of all the proposals that were submitted, the most affordable and the most advantageous using the cost – benefit method was selected, followed by a techno-economic analysis for the chosen proposal.
Keywords: Power generation; Electricity Authority of Cyprus; Παραγωγή Ηλεκτρικής ενέργειας; Αρχή Ηλεκτρισμού Κύπρου